Kesantunan Berbahasa pada Tuturan Anggota DPR Terkait Isu Tunjangan dan Demonstrasi 2025 (Kajian Pragmatik) - Maulidia, Ira; Mulyani, Sri (GERAM (Gerakan Aktif Menulis), 2026)
The issue of salary increases for members of the House of Representatives often sparks public discourse involving the dynamics of politeness and impoliteness in language. This study aims to analyze compliance with and violations of the principles of politeness in the speech of House of Representatives members regarding the issue of salary increases and the wave of demonstrations in 2025. This study employs a qualitative descriptive approach using content analysis. Subsequently, the data were analyzed descriptively using percentage tabulations to identify dominant politeness maxim trends. Data sources were obtained from various social media platforms containing both official statements and opinions of DPR members. Data were collected through observation and note-taking of 265 speech units, which were then analyzed using the theoretical framework of politeness maxims. The research results indicate that adherence to the maxims of politeness still dominates at 61%, while violations of the maxims (impoliteness) account for 39%. The maxim most frequently adhered to is the maxim of agreement, whereas the one most frequently violated is the maxim of modesty. The findings indicate that although the majority of utterances still adhere to public communication norms, the high number of violations reflects communication resistance and a lack of pragmatic empathy among political actors toward the sociocultural conditions of society. This has the potential to trigger an escalation of conflict between the public and the government; therefore, the application of Leech’s theory must take into account the cultural context and the dynamic nature of the communicative situation.